Strategy switches in proactive inhibitory control and their association with task-general and stopping-specific networks. (December 2019) - Messel, Mari S.; Raud, Liisa; Hoff, Per Kristian; Skaftnes, Cecilie Sol; Huster, René J.
Abstract: Prior information about the likelihood of a stop-signal pre-activates networks associated with response inhibition in both go- and stop-trials. How such prior information modulates the neural mechanisms enacting response inhibition is only poorly understood. To investigate this, a cued stop-signal task (with cues indicating stopping probabilities of 0%, 25% or 66%) was implemented in combination with functional magnetic resonance imaging (fMRI) data acquisition. Specifically, we focused on the effect of proactive inhibitory control as reflected in the activity of regions known to regulate response inhibition. Further, modulatory activity profiles in three different sub-regions of the right inferior frontal area were investigated. Behavioural results revealed an adaptation of task strategies through proactive control, with a possible gain for efficient inhibition at high stopping probabilities. The imaging data indicate that this adaption was supported by different regions traditionally involved in the stopping network. While the right inferior parietal cortex (IPC), right middle frontal gyrus (MFG), right inferior frontal gyrus (rIFG) pars triangularis, and left anterior insula all showed increased go-trial activity in the 0% condition compared to the 25% condition, the pre-supplementary motor area (pre-SMA), anterior midcingulate cortex (aMCC), right anterior insula, and the rIFG pars opercularis showed a more stopping-specific pattern, with stronger stop-trial activity in the 66% condition than in the 25% condition. Furthermore, activity in inferior frontal sub-regions correlated with behavioural changes, where more pronounced response slowing was associated with stronger activity increases from low to high stopping probabilities. Notably, the different right inferior frontal sub-regions showed different activity patterns in response to proactive inhibitory control modulations, supporting the idea of a functional dissociation within this area. Specifically, while the pars opercularis and the right insula showed stopping-related modulations of activity, the rIFG pars triangularis exhibited modulations only in go-trials with strong adaptions to fast responding or proactive slowing. Overall, the results indicate that proactive inhibitory control results in the switching of task or strategy modes, either favouring fast responding or stopping, and that these strategical adaptations are governed by an interplay of different regions of the stopping network. Highlights: A cued stop-signal task with different stopping probabilities was implemented. Behavioral and imaging results indicated an adaption of task strategies associated with different stopping probabilities. This adaption was governed by task-general and stopping specific networks. The results support a functional dissociation within the right inferior frontal area.